Searches for pulsar-like candidates from unidentified objects in the Third Catalog of Hard Fermi-LAT Sources with machine learning techniques. Issue 1 (24th April 2020) - Hui, C Y; Lee, Jongsu; Li, K L; Kim, Sangin; Oh, Kwangmin; Luo, Shengda; Leung, Alex P; Kong, A K H; Takata, J; Cheng, K S
ABSTRACT: We report the results of searching pulsar-like candidates from the unidentified objects in the Third Catalog of Hard Fermi -LAT Sources (3FHL). Using a machine-learning-based classification scheme with a nominal accuracy of $\sim \!98{{\, \rm per\, cent}}$, we have selected 27 pulsar-like objects from 200 unidentified 3FHL sources for an identification campaign. Using archival data, X-ray sources are found within the γ-ray error ellipses of 10 3FHL pulsar-like candidates. Within the error circles of the much better constrained X-ray positions, we have also searched for the optical/infrared counterparts and examined their spectral energy distributions. Among our shortlisted candidates, the most secure identification is the association of 3FHL J1823.3–1339 and its X-ray counterpart with the globular cluster Mercer 5. The γ-rays from the source can be contributed by a population of millisecond pulsars residing in the cluster. This makes Mercer 5 as one of the slowly growing hard γ-ray population of globular clusters with emission >10 GeV. Very recently, another candidate picked by our classification scheme, 3FHL J1405.1–6118, has been identified as a new γ-ray binary with an orbital period of 13.7 d. Our X-ray analysis with a short Chandra observation has found a possible periodic signal candidate of ∼1.4 h and a putative extended X-ray tail of ∼20 arcsec long. Spectral energy distribution of its optical/infrared counterpart conforms with a blackbody of T bb ∼ 40 000 K and R bb ∼ 12 R⊙ at a distance of 7.7 kpc. This is consistent with its identification as an early O star as found by infrared spectroscopy.